Analisis Penggunaan Metode Bercakap-Cakap Untuk Menstimulasi Kemampuan Berbicara Anak Pada Kelompok A - Hidayah, Rizka; Hariyanti, Dwi Prasetiyawati Diyah; Purwadi; Munawar, Muniroh; Pusari, Ratna Wahyu; Luthfy, Perdana Afif (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
The background of this study is children's speaking ability. Based on observations obtained: 1) Children are not yet able to answer simple questions given by the teacher. 2) Children feel embarrassed when speaking in front of their friends. 3) Children do not yet dare to express their ideas and opinions. This type of research uses Classroom Action Research. The data source of this study is based on informants and notes. The informants in this study were the principal and teachers of group A. The research subjects were 14 people. The data in this study were obtained through observation, interviews, and documentation. The results of the study showed that through the use of the Conversation Method, it can stimulate children's speaking ability such as children being able to use simple sentences in interacting, children being able to repeat stories with simple sentences, children being able to express ideas well, children being able to answer questions, enrich vocabulary, and being able to carry out 2-3 commands in sequence correctly. The suggestion that can be conveyed is that the role of parents and teachers is very important for children's speaking ability, so appropriate stimulation is needed.